The Strategy of Developing the Competence of Human Resources of the State Civil Apparatus of Barru Regency Government - Nur Ilmiah Rivai (Universitas Negeri Makassar, 2021)
This study aims to develop a Human Resources competency strategy at the Barru Regent's Office. This research specifically focuses on the development of Human Resources competencies used by the Barru district government in developing Human Resources apparatuses in order to perform high. This study uses a phenomenological approach, the main data collection techniques are interviews, observation Data analysis techniques used are data analysis techniques descriptive qualitative. The analysis was conducted after data collection through interviews and direct observation in the field. The results of the study include a strategy for developing resource management where competency-based apparatus people are realized by referring to the vision, mission, and goals through the remuneration mechanism as a form of appreciation for apparatus that has good performance. Development system and apparatus fulfillment system to improve apparatus competence, maintain productive human resources, improve welfare and create more positive competition. The whole process is carried out by referring to the principles of (a) human control control (b) recruit activity train, educate, develop, (d) manage Human relations performance, (e) reward and discipline action (f) manage redeployment, and (g) negotiation for working conditions.